Algorithm for Resecting Hepatocellular Carcinoma in the Caudate Lobe. Issue 6 (June 2021) - Takayama, Tadatoshi; Midorikawa, Yutaka; Higaki, Tokio; Nakayama, Hisashi; Moriguchi, Masamichi; Aramaki, Osamu; Yamazaki, Shintaro; Aoki, Masaru; Kogure, Kimitaka; Makuuchi, Masatoshi
Abstract : Objective: To propose an algorithm for resecting hepatocellular carcinoma (HCC) in the caudate lobe. Background: Owing to a deep location, resection of HCC originating in the caudate lobe is challenging, but a plausible guideline enabling safe, curable resection remains unknown. Methods: We developed an algorithm based on sublocation or size of the tumor and liver function to guide the optimal procedure for resecting HCC in the caudate lobe, consisting of 3 portions ( Spiegel, process, and caval) . Partial resection was prioritized to remove Spiegel or process HCC, while total resection was aimed to remove caval HCC depending on liver function. Results: According to the algorithm, we performed total (n = 43) or partial (n = 158) resections of the caudate lobe for HCC in 174 of 201 patients (compliance rate, 86.6%), with a median blood loss of 400 (10–4530) mL. Postoperative morbidity (Clavien grade ≥III b) and mortality rates were 3.0% and 0%, respectively. After a median follow-up of 2.6 years (range, 0.5–14.3), the 5-year overall and recurrence-free survival rates were 57.3% and 15.3%, respectively. Total and partial resection showed no significant difference in overall survival (71.2% vs 54.0% at 5 yr; P = 0.213), but a significant factor in survival was surgical margin (58.0% vs 45.6%, P = 0.034). The major determinant for survival was vascular invasion (hazard ratio 1.7, 95% CI 1.0–3.1, P = 0.026). Conclusions: Our algorithm-oriented strategy is appropriate for the resection of HCC originating in the caudate lobe because of the acceptable surgical safety and curability.